Report on Restructuring of the Planning Commission Volume-II Facilitators and Consultants - Planning Commission (Planning Commission, 2001)
To facilitate through structured consultation a continuous exchange of ideas and flow of information between government, experts and public at large with a view to get lateral inputs into the planning process, sensitise the civil society to impending policy changes and concerting the partners in the development process - the state, the market and the voluntary sector - towards attaining the national goal.
Asian Centre for Organisation Research and Development